Correcting for Systematic Underestimation of Topographic Glacier Aerodynamic Roughness Values From Hintereisferner, Austria - Chambers, Joshua R.; Smith, Mark W.; Smith, Thomas; Sailer, Rudolf; Quincey, Duncan J.; Carrivick, Jonathan L.; Nicholson, Lindsey; Mertes, Jordan; Stiperski, Ivana; James, Mike R. (Frontiers in Earth Science, 2021)
Spatially-distributed values of glacier aerodynamic roughness (z0) are vital for robust estimates of turbulent energy fluxes and ice and snow melt. Microtopographic data allow rapid estimates of z0 over discrete plot-scale areas, but are sensitive to data scale and resolution. Here, we use an extensive multi-scale dataset from Hintereisferner, Austria, to develop a correction factor to derive z0 values from coarse resolution (up to 30 m pixel) topographic data that are more commonly available over larger areas. Resulting z0 estimates are within an order of magnitude of previously validated, plot-scale estimates and aerodynamic values. The method is developed and tested using plot-scale microtopography data generated by structure from motion photogrammetry combined with glacier-scale data acquired by a permanent in-situ terrestrial laser scanner. Finally, we demonstrate the application of the method to a regional-scale digital elevation model acquired by airborne laser scanning. Our workflow opens up the possibility of including spatio-temporal variations of z0 within glacier surface energy balance models without the need for extensive additional field data collection.